Peranan Gaya Kepemimpinan Wanita dalam Upaya Meningkatkan Kinerja Pemasaran - Jusuf, Dewi Indriani; Narimawati, Umi; Sarwono, Jonathan (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This study aims to determine the role of women's leadership styles in improving marketing performance. In this study, the researcher uses meta-analysis and secondary data collection methods related to leadership theory. The findings of this research are: First, the leadership styles generally used by women leaders are 1) transformational leadership; 2) participative leadership or democratic leadership; and 3) visionary leadership. Second, the leadership styles used by women leaders contribute to improving  marketing performance through their efforts to empower employees to support their leadership while leading the business organization they run and by using leadership models that they consider appropriate and effective for leading and running their business activities.